Analysis of Aspects Required to Improve Customer Experience in Indonesia’s Internet Broadband - Wendy Junaidi (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2021)
In the digital age, transactions range from hailing a taxi to watching TV shows on demand that depend on an internet connection. As consumers have more power than ever before, today’s internet service providers face more demanding service expectations from customers than in the past, they recognize the need to improve certain aspects of business, including the quality of the experience they provide to customers. In other words, meeting the demands of broadband internet has its own challenges. The purpose of this study is to provide insights regarding challenges along the customer journey as the opportunities for improvement. The results showed that longer time from ordering to installation and frequent network disconnection are prioritized customer experience issues in internet broadband business and service providers need to focus on improving on the way companies engage the customers through reliable touch points and resetting the way people work in the organization to be more customer-centric.